Quset of the quiet mind - Holroyed Stuart (Willing -borough Northamptonshire, 1980)
first read this book in 1983 and it had a profound effect on me. Its a in depth concise summary of JK krishnamurti teachings and covers a wide spectrum in a brilliant manner. Its just as good today and will awaken any one on a spiritual search to new possibilities.
Keywords: Philosophy